VISUAL IMPAIRMENT IN NASOPHARYNGEAL CARCINOMA - Apryanza Akbar; Denny Satria Utama (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Introduction: he most common complaint in almost half of nasopharyngeal carcinoma (NPC) patients is a lump in the neck. Neurological symptoms occur less frequently, whereas blindness occurs in only less than one percent of cases. Case report: A 47-year-old male had complained about headache, nasal voice, and blindness in the right eye since a month ago. An examination found a mass in the right nasal cavity, right neck lymph nodes enlargement, damage to the right oculomotor (III), trochlear (IV), and abducens (VI) nerve, and right optic nerve (II). On funduscopy, the right macular reflex decreased. On CT scan there was a right nasopharyngeal mass extending to intracranial and right intraorbital spaces. Conclusion: There was a direct infiltration of NPC into surrounding and intracranial structures. Unilateral blindness might be caused by expansion to middle cerebral fossa and orbita. It could also be caused by optic nerve compression from surrounding tumor tissue.